NUSAYRÎLİKTEKİ AMCALIK GELENEĞİNİN YORUMLANMASI [THE INTERPRETATION OF UNCLE CUSTOM IN NUSAYRISM] - Gökçen ÇATLI ÖZEN (Türk Kültürü ve Hacı Bektaş Velî Araştırma Dergisi, 2018)
Every individual starts to acquire their cultural competence in childhood as a result of their interaction with their family and primary environment. For this reason, childhood is the first experience and the most important stage of socialising, forming the identity and creating a sense of belongingness. Going through transitions from childhood to adolescence and adulthood consecutively involves a usual process in most cultures, this can be done in a systematic, holy and secret ceremony in some other cultures. A good example of this ceremony is the local custom of uncle mediating between the male Nusayri child and his puberty. According to this custom, the acceptance of being a real Nusayri in the value of the community depends on the successful completion of the transitional ceremonies by the male child born in a Nusayri family. Nusayrism is considered to be Arabic Alawites according to some sources of information. It is widely argued that this classification can be generalized about Alevism and there can be a close resemblance between Anatolian or Turkish Alevism and Nusayrism in some sources. Taking everything into account, this article leads us to think in such an empirical way that each society and community can be said to have its own unique genetic fingerprints but in terms of social cohesion they need to meet in upper culture.